La muerte, la memoria y el olvido en escritos de Héctor Abad Faciolince (2014)
ABSTARCT: This article presents a reflection derived from a research process about six writings by Héctor Abad Facio-Lince, the author from Antioquia, Colombia, which share subjects of death, memory and oblivion. By means of texts that fluctuate between autobiographic narrative and argumentative prose, this writer proposes his ideas about the relationship of human beings with death, in particular when death violently snatches the beloved ones. The inter-textual reading shows a change in the way Abad deals with memory and oblivion: in the earlier texts he emphasizes on his efforts to preserve the memory of the beloved ones by means of writing, but in the later texts he remark on the importance of forgetting the wounds caused by violence.